Examining Social Value Orientations and Environmental Behaviour of the Riparian Communities along the Nairobi River, Kenya - Maureen Bosibori Ogega; Bessy Kathambi; Karatu Kiemo (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
It is widely believed that environmental conservation greatly contributes to reaching the Sustainable Development Goals (SDGs). Even so, social values are not given much attention when planning and carrying out environmental programs in urban riparian areas. For this reason, most efforts to encourage conservation among riparian communities are not well matched to local beliefs and do not reach their goals. In addition, a review of the literature reveals that most studies have focused only on environmental awareness, how policies work, and technical solutions. Therefore, this study aimed to discover how social values influence the environmental behavior of people living along the Nairobi River in Kenya. The study included 400 adults who lived within 500m of the Nairobi River in Nairobi County, Kenya. Data was gathered from the community by using questionnaires with psychometric scales and by interviewing key informants. Secondary data was gathered by reviewing documents and analyzing literature systematically. Most participants were found to have low concern for the environment (70%) and mainly held egoistic values about environmental matters. A positive linear relationship was found between social value orientations and both environmental behavior (R = 0.542) and environmental concern (R = 0.674). Therefore, the communities in the study area did not engage much with environmental issues. According to the study, most communities did not have complete environmental conservation programs (83.2%) or effective ways to manage waste (91.4%). The findings of this study will guide future policies for environmental programs to help Kenya achieve its sustainable urban development goals.